PENERAPAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 2 CALANG KABUPATEN ACEH JAYA - Mayang Somi; Linda Vitoria; Nurmasyitah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In IPAS learning in grade IV at SD Negeri 2 Calang, it was found that student learning outcomes were still low and had not reached the minimum competency standard (KKTP) of 75%. This was due to teacher-centered learning and the failure to relate the material to the cultural diversity of the students. This study aims to determine how the application of Culturally Responsive Teaching (CRT) can improve teacher activities, student activities, and learning outcomes in the subject matter “Unique Customs of the Community Around Me.” The research used a qualitative approach of Classroom Action Research (CAR) conducted in two cycles with 27 fourth-grade students as subjects. Data were collected through observation of teacher activities, observation of student activities, and learning outcome tests, then analyzed using qualitative descriptive analysis. The results showed that the application of CRT had a positive impact on the learning process and outcomes. Teacher activities improved from the good category in cycle I to very good in cycle II. Student activities also improved from good to very good, especially in terms of courage to ask questions, sharing family cultural stories, and cooperation in heterogeneous groups. Student learning outcomes also improved